1995
DOI: 10.1161/01.res.76.4.536
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthesis by Cultured Endothelial Cells Is Modulated by Flow Conditions

Abstract: In the present study, we examined the hypothesis that dynamic characteristics of flow modulate the production of vasoactive mediators, namely nitric oxide (NO) and endothelin-1 (ET-1), by human umbilical vein endothelial cells (HUVECs). Cells were exposed for 6 hours in a cone-and-plate apparatus to different types of flow: steady laminar, with shear stresses of 2, 8, and 12 dyne/cm2, pulsatile laminar, with shear stress from 8.2 to 16.6 dyne/cm2 and a frequency of 2 Hz; periodic laminar, with square wave cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
267
2
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(290 citation statements)
references
References 41 publications
19
267
2
2
Order By: Relevance
“…This was inevitably accompanied by a marked rise in blood viscosity, volume expansion, and increased shear stress, which can upregulate vascular and renal NOS expression. [21][22][23][24] These factors were clearly absent in our CRF group treated with EPO alone. Similarly, the goal of EPO replacement in patients with renal disease is the amelioration of CRF anemia as opposed to the induction of erythrocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…This was inevitably accompanied by a marked rise in blood viscosity, volume expansion, and increased shear stress, which can upregulate vascular and renal NOS expression. [21][22][23][24] These factors were clearly absent in our CRF group treated with EPO alone. Similarly, the goal of EPO replacement in patients with renal disease is the amelioration of CRF anemia as opposed to the induction of erythrocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured endothelial cells, laminar shear stress not only stimulated NO production but also eNOS expression. 25,26 Shear stress protected human umbilical venous endothelial cells from apoptosis induced by TNFa, 27,28 oxidative stress 28,29 or oxidized LDL 28 in culture, an effect that was partially blocked by L-NMMA. NO donors SNAP and sodium nitroprusside (SNP) further inhibited both TNFa and H 2 O 2 -induced apoptosis in these studies.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…In vitro studies suggest that these two distinct fluid stimuli (velocity acceleration vs. steady shear) regulate short-and longterm endothelial function via independent biomechanical pathways 70,71,[73][74][75] . Studies have shown that the rate of velocity acceleration can affect the progression of atherosclerosis 70,73,76) , endothelial cell function 71 , 74) , mechanotransduction 77,78) , calcium kinetics 79,80) , and vascular tone 81,82) . Conditions which affect velocity acceleration include ventricular ischemia 83) , acute myocardial infarction 84) , stenosis 85) , hypertension 86) , and hyperthyroidism 87) .…”
Section: Velocity Acceleration and Endothelial Functionmentioning
confidence: 99%